The Pengaruh Fraksi Massa Tepung Terigu Terhadap Hasil Hidroksiapatit Dengan Prekursor Cangkang Bekicot Menggunakan Metode Sol-Gel - Pakpahan, Greynaldi; Adoe, Dominggus G. H.; Limbong, Ishak (Universitas Nusa Cendana, 2024)
This research aims to determine the effect of the mass fraction of wheat flour (Triticum aestivum L) on the results of porous hydroxyapatite with snail shell precursors (Lissachatina fulica). The method used in this research is the Sol-Gel method with a sintering temperature of 1000°C and a sintering time of 5 hours with a mass fraction between wheat flour (Triticum aestivum L) and snail shell powder (Lissachatina fulica) of 60%, 50%, 40%, and 100%. Density, porosity and SEM characterization tests were used in this study to determine the density value, porosity value, and pore size of the porous hydroxyapatite sample. In this density test using Archimedes' law, it shows that the four samples (A1 + B1, A2 + B2, A3 + B3, and A4) have density values of 0.145 g/cm3, 0.15 g/cm3, 0.1967 g/cm3, and 0.221 g/cm3. In porosity testing, the three samples with mass fractions between snail shell powder and wheat flour will be compared with one pure sample of only snail shell, which obtained porosity values of 34.39%, 32.13%, and 11%. Finally, the SEM characterization found that the pore size of the porous hydroxyapatite sample has a size range from 34.5228 µm - 71.7012 µm.